Pomegranate Consumption and Blood Pressure: A Review - Asgary, Sedigheh; Keshvari, Mahtab; Sahebkar, Amirhossein; Sarrafzadegan, Nizal (Current Pharmaceutical Design, 2017)
Background: Pomegranate (Punica granatum L.) is a polyphenol-rich fruit with diverse medicinal properties. Several lines of experimental and clinical evidence have shown that pomegranate intake helps lowering blood pressure (BP) through different mechanisms. Aims: This study aimed to present a narrative review on the anti-hypertensive properties of different parts of pomegranate such as pomegranate juice (PJ), pomegranate peels (PP), pomegranate seed oil (PSO), pomegranate fruit extract (PFE) and the mechanisms and phytochemicals responsible for these effects. Methods: A review on the efficacy of consuming different parts of pomegranate (juice, peels, fruit extract and seed oil) in lowering BP has been performed. To find relevant studies, a search in PubMed, Science Direct and Scopus up from inception to May 4, 2015 was performed. Human, animals and in vitro studies investigating the anti-hypertensive effects of pomegranate were included in the search. Results: Findings arising from animal and clinical studies have shown pomegranate juice can reduce BP in both short-term and long-term course. These effects are accompanied by antioxidant and anti-atherosclerotic actions that collectively improve cardiovascular health. The anti-hypertensive effects have been reported for both pomegranate juice and seed oil. Both systolic and diastolic pressures are affected. Conclusion: Pomegranate juice possesses antioxidant, anti-hypertensive and anti-atherosclerotic properties.
Keywords: Pomegranate